Muda Berkarya Motivasi Wirausaha Dalam Kajian Fenomenologi - Nuri Purwanto (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2020)
The focus of the study is to uncover entrepreneurial experiences and entrepreneurial strategies that are specific to each subject. Research subjects used a purposive technique. The desired characteristics of the subject are an entrepreneur or entrepreneur who is under the age of 24 years and is willing to be the subject of research. Data collection methods using interviews, In this study using a qualitative methodology with a phenomenological approach, from the interviews it was found that entrepreneurs use social media as a means to develop their business because of three things, namely: (1) efficient, cost-saving, (2) effective , in searching for consumers and promotions, (3) strategic innovation, as a solution for increasingly receding offline sales